Implementation Model of Guidance by School Supervisors in Junior High Schools - Silow, Susanti; Lengkong, Jeffry S.J.; Usoh, Elni J.; Mongdong, Romi J. (Abdurrauf Science and Society, 2025)
This study aims to describe the implementation model of mentoring by school supervisors at State Junior High School 2 Amurang in South Minahasa Regency. This study uses a qualitative approach and case study method. The location of the study is State Junior High School 2 Amurang in South Minahasa Regency. The sources of research data are informants of school supervisors, principals, homeroom teachers and subject teachers. The data of this study were collected using interviews, observation, and documentation study techniques and processed using qualitative data analysis techniques, namely the interaction model. The results of the study indicate that the implementation model of mentoring by school supervisors is a cycle consisting of four stages of mentoring starting from the planning stage of school mentoring, the mentoring stage for planning school work programs, the mentoring stage for implementing school work programs, and the reporting stage of school mentoring results. After discussing the research findings, it is continued by compiling research conclusions and recommendations that are recommendatory.